Laminated ceramic electronic component and method for manufacturing same

By introducing conductive metal and silicon-containing glass into the external electrodes of the laminated ceramic electronic components, and forming a pore structure, the problem of deterioration of insulation resistance caused by hydrogen ion diffusion in the plating process is solved, and the moisture resistance of the components is improved.

CN120226108APending Publication Date: 2025-06-27MURATA MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380080166.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2023-12-08
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

In the laminated ceramic electronic components, the plating process of the external electrodes leads to the generation of hydrogen ions, which pass through the ceramic layer, resulting in deterioration of insulation resistance.

Method used

By introducing conductive metal and silicon-containing glass into the external electrodes, and controlling the temperature during the firing process, more than 20 pores with a length diameter of more than 20 nm and less than 600 nm are formed so that hydrogen ions can be vaporized in these pores and preventing them from diffusing to the ceramic layer.

Benefits of technology

It effectively suppresses the diffusion of hydrogen ions on the ceramic layer, reduces the influence of hydrogen ions on the insulation resistance, and improves the moisture resistance and reliability of stacked ceramic electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120226108A_ABST
    Figure CN120226108A_ABST
Patent Text Reader

Abstract

Provided is a laminated ceramic electronic component capable of reducing the influence of hydrogen ions generated during a plating process of an external electrode on a ceramic layer. A laminated ceramic electronic component is provided with a ceramic body (2) having a plurality of laminated ceramic layers (3) and internal electrodes (4) disposed along the interfaces between the ceramic layers (3), external electrodes (6) provided on the surface of the ceramic body (2) and electrically connected to the internal electrodes (4), and a plating film formed on the external electrodes (6), the external electrode (6) contains a conductive metal (11) and a silicon-containing glass (13), and when a cross-section of the external electrode (6) along the thickness direction is observed, there are 20 or more pores (12) having a major axis of 20-600 nm in a range in which the thickness-direction dimension at the center in the thickness direction is 1 [mu] m and the width-direction dimension orthogonal to the thickness direction is 5 [mu] m. Hydrogen ions are gasified in the pores (12), and diffusion of the hydrogen ions into the ceramic body (2) is suppressed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multilayer ceramic electronic component and a method for manufacturing the same, and more particularly to a structure of an external electrode provided on the surface of a ceramic body included in the multilayer ceramic electronic component and a method for forming the same. Background Art

[0002] As a technology of interest for the present invention, for example, Japanese Patent Laid-Open No. 1-80011 (Patent Document 1) discloses that in a multilayer ceramic capacitor, hydrogen ions are generated by a chemical reaction during a plating process of an external electrode, and these hydrogen ions are occluded by an internal electrode, gradually reducing the surrounding dielectric ceramic layer and causing problems such as deterioration of the insulation resistance. As a solution to this problem, Patent Document 1 discloses that when the internal electrode is mainly composed of a noble metal (e.g., an Ag-Pd alloy), a metal that deactivates hydrogen absorption (e.g., Ni) is added to the internal electrode.

[0003] Prior Art Documents

[0004] Patent Documents

[0005] Patent Document 1: Japanese Patent Laid-Open No. 1-80011 Summary of the Invention

[0006] Problems to be Solved by the Invention

[0007] In recent years, in order to reduce material costs, it has become more common to use base metals such as Ni as the material of the internal electrode instead of noble metals such as Ag and Pd. In addition, Patent Document 1 discloses that Ni is a metal that deactivates hydrogen absorption. However, according to the research of the inventors of the present invention, it has been found that even when the internal electrode contains Ni, the influence of hydrogen cannot be completely avoided, and the insulation resistance of the dielectric ceramic layer is more or less deteriorated.

[0008] The same problem is not limited to multilayer ceramic capacitors, and is also commonly encountered in multilayer ceramic electronic components including a ceramic body, an external electrode provided on the surface of the ceramic body and electrically connected to the internal electrode, and a plating film formed on the external electrode, where the ceramic body has a plurality of laminated ceramic layers and internal electrodes arranged along the interfaces between the ceramic layers.

[0009] Therefore, an object of the present invention is to provide a multilayer ceramic electronic component and a method for manufacturing the same that can reduce the influence of hydrogen ions generated by a chemical reaction during the plating process of an external electrode on the ceramic layer.

[0010] Technical Means for Solving the Problems

[0011] In the present invention, in order to solve the above technical problems, the structure of the external electrodes in the multilayer ceramic electronic component is improved. In addition, a method for forming such improved external electrodes is provided.

[0012] More specifically, the ceramic electronic component according to the present invention includes: a ceramic body having a plurality of stacked ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers; external electrodes provided on the surface of the ceramic body and electrically connected to the internal electrodes; and a plating film formed on the external electrodes.

[0013] It is characterized in that the external electrodes contain a conductive metal and a glass containing silicon, and when observing a cross-section of the external electrodes along the thickness direction, within a range where the thickness direction dimension at the central portion in the thickness direction is 1 μm and the width direction dimension orthogonal to the thickness direction is 5 μm, there are 20 or more pores having a major axis of 20 nm or more and 600 nm or less.

[0014] The manufacturing method of the multilayer ceramic electronic component according to the present invention is directed to a manufacturing method of a ceramic electronic component including a ceramic body having a plurality of stacked ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers, external electrodes provided on the surface of the ceramic body and electrically connected to the internal electrodes, and a plating film formed on the external electrodes, and is characterized by including the following steps.

[0015] Including:

[0016] A step of preparing a conductive material in a sol state, the conductive material in a sol state containing (1) a conductive metal salt that becomes a conductive metal as a conductive component through firing, (2) a glass raw material that becomes a glass containing silicon and contains a glass metal salt through firing, and (3) a solvent that dissolves or disperses the conductive metal salt and the glass raw material, and the glass raw material having a given softening point and melting point;

[0017] A step of applying the conductive material to the surface of the ceramic body in order to form the external electrodes so as to be in contact with the internal electrodes;

[0018] Next, a step of heating and drying the conductive material to gel it;

[0019] Next, a step of firing at a temperature above the softening point and below the melting point of the glass raw material and above the melting point of the glass metal salt to form the external electrodes; and

[0020] A step of forming a plating film on the external electrodes.

[0021] Advantages of the Invention

[0022] According to the present invention, hydrogen ions generated during plating and entering the external electrode are vaporized in the pores of the external electrode, which can suppress the diffusion into the ceramic body and reduce the influence of hydrogen ions on the ceramic layer.

[0023] In addition, according to the manufacturing method of the multilayer ceramic electronic component of the present invention, the conductive metal salt contained in the conductive material for forming the external electrode undergoes volume shrinkage when metallized by heat drying and firing. On the other hand, the firing temperature is selected to be above the softening point and below the melting point of the glass, so pores can be formed. In this case, since the conductive material is in a sol state, the conductive metal salt and the glass raw material are in a highly dispersed state at the nanoscale. Therefore, even in a thin external electrode with a film thickness of, for example, 1 μm, submicron-sized pores with a major axis of 20 nm or more and 600 nm or less can be uniformly and abundantly generated. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 FIG. is a cross-sectional view schematically showing a multilayer ceramic capacitor 1 as a multilayer ceramic electronic component according to an embodiment of the present invention.

[0025] Figure 2 It is Figure 1 A cross-sectional view schematically showing an enlarged portion of the multilayer ceramic capacitor 1 provided with the external electrode 6 shown.

[0026] Figure 3 FIG. is a diagram showing a SIM image of an FIB cross-section of a portion of the multilayer ceramic capacitor related to the specimen 5 fabricated in the experimental example, and is obtained by photographing a portion corresponding to Figure 2 a part of the region shown. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0027] Refer to Figure 1 and the structure of the multilayer ceramic capacitor 1 as a multilayer ceramic electronic component according to an embodiment of the present invention will be described.

[0028] The multilayer ceramic capacitor 1 includes a ceramic body 2. The ceramic body 2 includes a plurality of stacked ceramic layers 3, and a plurality of internal electrodes 4 and 5 disposed along the interfaces between the plurality of ceramic layers 3. The internal electrodes 4 and 5 are classified into a plurality of first internal electrodes 4 and a plurality of second internal electrodes 5 that are alternately disposed in the stacking direction of the ceramic body 2. On the surfaces of the ceramic body 2, more specifically, on the opposite end faces, a first external electrode 6 and a second external electrode 7 are respectively provided. The first external electrode 6 is electrically connected to the first internal electrode 4, and the second external electrode 7 is electrically connected to the second internal electrode 5.

[0029] The ceramic layer 3 includes a dielectric ceramic having, for example, ABO3 (where A is at least one of Ba, Ca, and Sr, and B is at least one of Ti and Zr) as a main component. In addition, the dielectric ceramic may have the above ABO3 as a main component and contain at least one of Mn, Mg, Si, Y, Dy, and Gd as a sub-component.

[0030] The internal electrodes 4 and 5 preferably contain a conductive metal or an alloy containing a conductive metal. For example, it is preferable to contain one selected from nickel, copper, silver, and a silver / palladium alloy as a conductive component.

[0031] The external electrodes 6 and 7 are formed by applying a conductive material described later to the end faces of the ceramic body 2 so as to be in contact with the respective ends of the internal electrodes 4 and 5, heating and drying the same, and then baking. In Figure 2 a part of the first external electrode 6 is shown in a cross-sectional view. In addition, although the second external electrode 7 is not shown in Figure 2 it has substantially the same structure as the first external electrode 6. A plating film 8 is formed on the external electrodes 6 and 7 (not shown in Figure 1 ).

[0032] The multilayer ceramic capacitor 1 is manufactured, for example, through the following steps. First, a ceramic slurry containing raw material powder of a ceramic having the above-described composition is prepared. Next, an appropriate sheet forming method is applied to the ceramic slurry to form a green ceramic sheet. Next, a conductive paste to be the internal electrodes 4 and 5 is applied by printing or the like on a given green ceramic sheet among a plurality of green ceramic sheets. Next, the plurality of green ceramic sheets are laminated and then pressed to obtain an unprocessed ceramic body. Next, the unprocessed ceramic body is fired. In this firing step, the green ceramic sheets become the ceramic layer 3. After that, a step of forming the external electrodes 6 and 7 on the end faces of the ceramic body 2 is performed, and then a step of forming the plating film 8 on the external electrodes 6 and 7 is performed.

[0033] The conductive material for forming the external electrodes 6 and 7 is initially in a sol state and contains (1) a conductive metal salt that becomes a conductive metal as a conductive component through firing, (2) a glass raw material that becomes a glass containing silicon through firing and contains a glass metal salt, and (3) a solvent that dissolves or disperses the conductive metal salt and the glass raw material. The above glass raw material has a given softening point and melting point.

[0034] Such a conductive material is applied to opposite end faces of the ceramic body 2 in a sol state. Next, after heating and drying to become a gel state, firing is performed at a temperature above the softening point and below the melting point of the above glass raw material and above the melting point of the metal salt for glass, thereby vitrifying the glass raw material. In this way, since the firing temperature is set above the softening point and below the melting point of the glass and above the melting point of the metal salt for glass, the glass in the external electrodes 6 and 7 can ensure the close contact between the conductive metals within the external electrodes 6 and 7 and the close contact between the external electrodes 6 and 7 and the base surface 10, and a uniform and numerous number of pores can be generated within the external electrodes 6 and 7.

[0035] More specifically, when observing a cross-section of the external electrodes 6 and 7 along the thickness direction, within a range where the dimension in the thickness direction at the central portion in the thickness direction is 1 μm and the dimension in the width direction orthogonal to the thickness direction is 5 μm, 20 or more submicron-sized pores with a major axis of 20 nm or more and 600 nm or less can be uniformly generated.

[0036] Preferably, 41 or more pores exist within the above range. On the other hand, the upper limit of the number of pores is not particularly limited, but in the experimental examples described later, it was confirmed that the upper limit of the number of pores was 227 within the above range.

[0037] The glass raw material contained in the above conductive material preferably contains nano-silica and boric acid in addition to the above metal salt for glass.

[0038] The metal salt for glass as the glass raw material contains, for example, lithium nitrate and sodium nitrate.

[0039] The conductive metal salt contained in the conductive material preferably contains either a metal nitrate or a metal carboxylate. The metal nitrate contains, for example, copper nitrate.

[0040] In the conductive material, the ratio of the content of the glass raw material to the content of the conductive metal salt, in terms of the mass after metallization of the conductive metal salt and the mass after vitrification of the glass raw material, is preferably 0.04 or more and 1.40 or less.

[0041] The solvent contained in the conductive material contains, for example, diethylene glycol monoethyl ether.

[0042] In order to perform viscosity adjustment, etc., the conductive material may also contain an organic binder. As the organic binder, for example, hydroxypropyl cellulose is advantageously used.

[0043] Regarding the plating film 8 formed on the external electrodes 6 and 7, although not illustrated in detail, it is composed of, for example, a Cu plating layer, an Ni plating layer thereon, and an Sn plating layer thereon.

[0044] As described above, the present invention has been described in relation to the external electrodes of a multilayer ceramic capacitor. However, the present invention can also be applied to multilayer ceramic electronic components other than multilayer ceramic capacitors, provided that the components have a laminated ceramic body having a plurality of laminated ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers, and external electrodes electrically connected to the internal electrodes are provided on the surface of the ceramic body.

[0045] In addition, as the conductive material for forming the external electrodes 6 and 7, copper was used in the following experimental examples as the conductive component, but it may also be a conductive metal other than copper.

[0046] Next, experimental examples carried out to confirm the effects of the present invention will be described.

[0047] <Fabrication of Conductive Material>

[0048] The following (1) to (7) were mixed in the mass percentages shown in Table 1 to fabricate a conductive material in a sol state.

[0049] (1) 50-nm diameter nano silica surface-treated with methacrylic silane (“ADMANANO” manufactured by Admatechs)

[0050] (2) Boric acid

[0051] (3) Lithium nitrate (melting point: 260°C)

[0052] (4) Sodium nitrate (melting point: 306°C)

[0053] (5) Copper(II) nitrate trihydrate

[0054] (6) Hydroxypropyl cellulose (2.0 to 2.9 @ 20°C / 2% aqueous solution)

[0055] (7) Diethylene glycol monoethyl ether

[0056] The above (1) to (4) are glass raw materials that become glass through firing, (3) and (4) are metal salts for glass, (5) is a conductive metal salt that becomes a conductive metal through firing, (6) is an organic binder, and (7) is a solvent.

[0057] In Table 1, the ratio of the content of the glass raw material to the content of copper(II) nitrate trihydrate as the conductive metal salt, i.e., “glass / Cu”, is shown in terms of the mass after metallization of the conductive metal salt and the mass after vitrification of the glass raw material.

[0058] <Measurement of Softening Point / Melting Point of Glass Raw Material>

[0059] The following solution was dried at 120 °C for 30 minutes.

[0060] · 50 nm diameter nano-silica surface-treated with silane methacrylate (“ADMANANO” manufactured by Admatechs): 0.92 mass%,

[0061] · Boric acid: 0.55 mass%,

[0062] · Lithium nitrate: 0.29 mass%,

[0063] · Sodium nitrate: 0.39 mass%.

[0064] For the obtained dried solid, TG-DTA (TP-1 manufactured by Rigaku) was performed in N2 under the following conditions. Based on its behavior, the softening point of the glass was estimated to be 545 °C and the melting point to be 716 °C.

[0065] · Room temperature to 950 °C (20 °C / minute),

[0066] · N2 flow rate: 300 ml / minute,

[0067] · Specimen container: made of alumina,

[0068] · Specimen amount: 10 mg.

[0069] <Coating / Firing>

[0070] After dipping the end face of the ceramic body of a multilayer ceramic capacitor (0.6 mm × 0.3 mm × 0.3 mm) with a Ni internal electrode into the above-mentioned conductive material in sol form, the conductive material was dried at 120 °C for 30 minutes to gel. The opposite end face of the ceramic body was also dipped and dried in the same manner.

[0071] Next, hydrogen was introduced in N2 and firing was performed at 700 °C, which is above the softening point and below the melting point of the glass and above the melting point of the metal salt of the glass, to form an external electrode as a fired film containing pores in Cu particles and glass.

[0072] <Structural Analysis of External Electrode>

[0073] At the center of the surfaces of the multilayer ceramic capacitor that extend in the width direction and the thickness direction, FIB (Focused Ion Beam) processing (Hitachi High-Technologies "SMI-3050R") was performed on the external electrodes that became the specimens, and the pores that appeared on the processed surface were observed by SIM (Scanning Ion Microscope). More specifically, within a range where the thickness direction dimension of the external electrode was 1 μm and the width direction dimension orthogonal to the thickness direction was 5 μm, the pores were observed, and as shown in Table 1, the "number of pores", "minimum pore", and "maximum pore" were obtained. The "number of pores" represents the number of pores within the above range, the "maximum pore" represents the major axis of the largest pore among the pores within the above range, and the "minimum pore" represents the major axis of the smallest pore among the pores within the above range.

[0074] <Plating>

[0075] For the external electrodes, electrolytic Cu, Ni, and Sn plating were successively performed based on the following conditions to form a plated film.

[0076] (Cu plating conditions)

[0077] · Plating bath type: Cupric pyrophosphate plating bath (pH = 8.6),

[0078] · Bath temperature: 55 °C,

[0079] · Current value: 10 A,

[0080] · Plating time: 90 minutes.

[0081] (Ni plating conditions)

[0082] · Plating bath type: Watts bath (pH = 4.0),

[0083] · Bath temperature: 60 °C,

[0084] · Current value: 6 A,

[0085] · Plating time: 51 minutes.

[0086] (Sn plating conditions)

[0087] · Plating bath type: Neutral plating bath (pH = 6.0),

[0088] · Bath temperature: 25 °C,

[0089] · Current value: 3 A,

[0090] · Plating time: 66 minutes.

[0091] <Capacitance measurement>

[0092] Using an LCR meter (HEWLETT PACKARD's "HP4984A"), the capacitance of the multilayer ceramic capacitor specimens after plating formation was measured under the conditions of 1 kHz / 0.5 Vrms. Based on the evaluation of the measurement results, in the "Capacitance" column of Table 1, "○" is used when the expected value can be ensured, and "×" is used when the expected value cannot be ensured.

[0093] <Moisture Resistance Reliability Evaluation>

[0094] For the multilayer ceramic capacitor specimens, a PCBT (Pressure Cooker Bias Test) was conducted under the conditions of a temperature of 125°C, a relative humidity of 95%, an applied voltage of 3.2 V, a load time of 72 hours, and 15 specimens. For each specimen, the insulation resistance (IR) was measured, and a decrease in the LogIR value by 0.5 at the end of the test compared to the start of the test was regarded as IR degradation. In the "Moisture Resistance Reliability" column of Table 1, "○" is used when there are no specimens with IR degradation, and "×" is used when there are specimens with IR degradation.

[0095] [Table 1]

[0096] Table 1

[0097]

[0098] In Table 1, specimens 1 to 7 satisfied the condition of having 20 or more pores with a major axis of 20 nm or more and 600 nm or less. Among these specimens 1 to 7, the evaluation of "Moisture Resistance Reliability" was "○". In contrast, for specimen 8 that did not satisfy the above condition, the evaluation of "Moisture Resistance Reliability" was "×".

[0099] Regarding the multilayer ceramic capacitors of specimens 1 to 7, since while ensuring conduction and adhesion in the external electrodes, there are fine pores highly dispersed in the external electrodes, having a structure that can vaporize hydrogen atoms, it is possible to suppress the diffusion of hydrogen generated during plating and invading the external electrodes into the ceramic layer, and prevent the degradation of the insulation resistance.

[0100] Although not shown in Table 1, the capacitance was also evaluated. As a result, it was confirmed that there were no problems with the capacitance for specimens 1 to 8.

[0101] In addition, if we focus on the "Glass / Cu" in Table 1, it can be seen that among specimens 2 to 7 where it is in the range of 0.04 or more and 1.40 or less, the evaluation of "Moisture Resistance Reliability" is "○", and it is more preferable for "Glass / Cu" to be in the range of 0.04 or more and 1.40 or less.

[0102] In the above-described specimens 2 to 7, the "number of pores" falls within the range of 41 or more and 227 or less. Therefore, from the perspective of the "number of pores", it can be said that a range of 41 or more and 227 or less is more preferable.

[0103] Figure 3 is a SIM image of a cross-section of the external electrode related to Specimen 5 based on FIB processing. In Figure 3 For, the elements corresponding to the elements shown in Figure 1 and Figure 2 are labeled with the same reference numerals.

[0104] In Figure 3 what appears at the lower part is the end face from which the internal electrode 4 in the ceramic body 2 is led out, and the external electrode 6 is located thereon. In the external electrode 6, the relatively bright spots are Cu11, and in the vicinity of the end face of the ceramic body 2, the relatively dark spots that are densely distributed are pores 12, and the gray areas other than these are glass 13.

[0105] Although not shown in Table 1, specimens related to comparative examples were produced by performing the same operations as in the case of Specimen 5 except for removing lithium nitrate and sodium nitrate from the solution composition of the conductive material in the sol state of Specimen 5. As a result, in this comparative example, peeling occurred in the external electrode after firing and plating. It is presumed that since there are no metal salts (lithium nitrate and sodium nitrate) that exceed the melting point during firing, the welding at the base surface of the inside and outside of the external electrode does not easily progress, and the fixing property of the external electrode cannot be ensured.

[0106] In an embodiment of the present invention, there is a mode as follows.

[0107] <1>

[0108] A multilayer ceramic electronic component, comprising:

[0109] a ceramic body having a plurality of stacked ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers;

[0110] an external electrode provided on the surface of the ceramic body and electrically connected to the internal electrode; and

[0111] a plating film formed on the external electrode,

[0112] the external electrode includes a conductive metal and a glass containing silicon,

[0113] When observing a cross-section of the external electrode along the thickness direction, within a range where the dimension in the thickness direction at the central portion in the thickness direction is 1 μm and the dimension in the width direction orthogonal to the thickness direction is 5 μm, there are 20 or more pores having a major axis of 20 nm or more and 600 nm or less.

[0114] <2>

[0115] In the multilayer ceramic electronic component described in <1>, there are 41 or more of the pores within the above range.

[0116] <3>

[0117] In the multilayer ceramic electronic component described in <1> or <2>, there are 227 or less of the pores within the above range.

[0118] <4>

[0119] In the multilayer ceramic electronic component described in any one of <1> to <3>, the multilayer ceramic electronic component is a multilayer ceramic capacitor.

[0120] <5>

[0121] A method for manufacturing a multilayer ceramic electronic component, the ceramic electronic component including: a ceramic body having a plurality of laminated ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers; an external electrode provided on the surface of the ceramic body and electrically connected to the internal electrodes; and a plating film formed on the external electrode,

[0122] wherein the method for manufacturing the multilayer ceramic electronic component includes:

[0123] a step of preparing a conductive material in a sol state, the sol state conductive material including (1) a conductive metal salt that becomes a conductive metal as a conductive component through firing, (2) a glass raw material that becomes a glass containing silicon through firing and contains a glass metal salt, and (3) a solvent that dissolves or disperses the conductive metal salt and the glass raw material, the glass raw material having a given softening point and melting point;

[0124] a step of applying the conductive material to the surface of the ceramic body so as to be in contact with the internal electrodes in order to form the external electrode;

[0125] next, a step of heating and drying the conductive material to gel it;

[0126] next, a step of firing at a temperature equal to or higher than the softening point of the glass raw material and lower than the melting point thereof, and at a temperature equal to or higher than the melting point of the glass metal salt, so as to form the external electrode; and

[0127] The step of forming a plating film on the external electrode.

[0128] <6>

[0129] In the method for manufacturing a multilayer ceramic electronic component according to <5>, the glass raw material contains nano-silica and boric acid in addition to the metal salt for glass.

[0130] <7>

[0131] In the method for manufacturing a multilayer ceramic electronic component according to <5> or <6>, the metal salt for glass contains lithium nitrate and sodium nitrate.

[0132] <8>

[0133] In the method for manufacturing a multilayer ceramic electronic component according to any one of <5> to <7>, the conductive metal salt contains either a metal nitrate or a metal carboxylate.

[0134] <9>

[0135] In the method for manufacturing a multilayer ceramic electronic component according to <8>, the metal nitrate contains copper nitrate.

[0136] <10>

[0137] In the method for manufacturing a multilayer ceramic electronic component according to any one of <5> to <9>, the ratio of the content of the glass raw material to the content of the conductive metal salt, in terms of the mass after metallization of the conductive metal salt and the mass after vitrification of the glass raw material, is 0.04 or more and 1.40 or less.

[0138] <11>

[0139] In the method for manufacturing a multilayer ceramic electronic component according to any one of <5> to <10>, the solvent contains diethylene glycol monoethyl ether.

[0140] <12>

[0141] In the method for manufacturing a multilayer ceramic electronic component according to any one of <5> to <11>, the conductive material further contains an organic binder.

[0142] <13>

[0143] In the method for manufacturing a multilayer ceramic electronic component according to <12>, the organic binder contains hydroxypropyl cellulose.

[0144] Explanation of reference numerals

[0145] 1 Multilayer ceramic capacitor

[0146] 2 Ceramic body

[0147] 3 Ceramic layer

[0148] 4, 5 Internal electrodes

[0149] 6, 7 External electrodes

[0150] 8 Coating film

[0151] 11 Cu

[0152] 12 Pores

[0153] 13 Glass.

Claims

1. A multilayer ceramic electronic component, comprising: A ceramic body having a plurality of stacked ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers; External electrodes provided on the surface of the ceramic body and electrically connected to the internal electrodes; and A plating film formed on the external electrodes, The external electrodes include a conductive metal and a glass containing silicon, When observing a cross-section of the external electrode along the thickness direction, within a range where the thickness direction dimension at the central portion in the thickness direction is 1 μm and the width direction dimension orthogonal to the thickness direction is 5 μm, there are 20 or more pores having a major axis of 20 nm or more and 600 nm or less.

2. The multilayer ceramic electronic component according to claim 1, wherein There are 41 or more of the pores within the range.

3. The multilayer ceramic electronic component according to claim 1 or 2, wherein There are 227 or less of the pores within the range.

4. The multilayer ceramic electronic component according to any one of claims 1 to 3, wherein The multilayer ceramic electronic component is a multilayer ceramic capacitor.

5. A method for manufacturing a multilayer ceramic electronic component, the ceramic electronic component comprising: a ceramic body having a plurality of stacked ceramic layers and internal electrodes disposed along the interfaces between the ceramic layers; and external electrodes provided on the surface of the ceramic body and electrically connected to the internal electrodes; And a plating film formed on the external electrodes, Wherein The method for manufacturing the multilayer ceramic electronic component includes: A step of preparing a sol-state conductive material, the sol-state conductive material including (1) a conductive metal salt that becomes a conductive metal as a conductive component through firing, (2) a glass raw material that becomes a glass containing silicon and contains a glass metal salt through firing, and (3) a solvent that dissolves or disperses the conductive metal salt and the glass raw material, and the glass raw material has a given softening point and melting point; A step of applying the conductive material to the surface of the ceramic body to be in contact with the internal electrodes in order to form the external electrodes; Next, a step of heating and drying the conductive material to gelify it; Next, a step of firing at a temperature above the softening point of the glass raw material and below the melting point and at a temperature above the melting point of the glass metal salt to form the external electrodes; and A step of forming a plating film on the external electrodes.

6. The method for manufacturing the multilayer ceramic electronic component according to claim 5, wherein The glass raw material further includes nano-silica and boric acid in addition to the glass metal salt.

7. The method for manufacturing the multilayer ceramic electronic component according to claim 5 or 6, wherein The glass metal salt includes lithium nitrate and sodium nitrate.

8. The method for manufacturing the multilayer ceramic electronic component according to any one of claims 5 to 7, wherein The conductive metal salt includes either metal nitrate or metal carboxylate.

9. The method for manufacturing the multilayer ceramic electronic component according to claim 8, wherein The metal nitrate includes copper nitrate.

10. The method for manufacturing the multilayer ceramic electronic component according to any one of claims 5 to 9, wherein The ratio of the content of the glass raw material to the content of the conductive metal salt, in terms of the mass after metallization of the conductive metal salt and the mass after vitrification of the glass raw material, is 0.04 or more and 1.40 or less.

11. The method for manufacturing a multilayer ceramic electronic component according to any one of claims 5 to 10, wherein the solvent contains diethylene glycol monoethyl ether.

12. The method for manufacturing a multilayer ceramic electronic component according to any one of claims 5 to 11, wherein the conductive material further contains an organic binder.

13. The method for manufacturing a multilayer ceramic electronic component according to claim 12, wherein the organic binder contains hydroxypropyl cellulose.

Citation Information

Patent Citations

  • Laminated ceramic capacitor

    JP1989080011A